DATA ANALYTICS AND ITS METHODS OF DEVELOPMENT - Zebiniso Igamberdieva (Web of Journals Publishing, 2024)
The article discusses characteristics of data analysis and what role does different types of data analysis play in collecting informations? Data analysis is a technique used by academics to turn data into a narrative and then interpret it to draw conclusions. Different techniques such as modeling to reach trends, relationships, and therefore conclusions to address the decision-making process are employed in this process.
Keywords: Data analysis, descriptive, exploratory, inferential, predictive, explanatory or causal, mechanistic, data analysis process, data collection, data decision, data cleaning, data analysis, data interpretation, data visualization.